Pengaruh Gaya Kepemimpinan Otoriter dan Kompensasi Financial terhadap Kinerja Karyawan dengan Disiplin Kerja sebagai Variabel Intervening pada PT. Gudang Garam Tbk. - Gohan Yuli Darmawan; Eko Widodo; Indah Yuni Astuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is based on a phenomenon about the leadership style of PT. Gudang Garam Tbk which is authoritarian. In addition, there is also the problem of compensation in the form of overtime wages which are unevenly distributed by PT Gudang Garam Tbk. In this case, if allowed to drag on, it can affect the level of discipline owned by each personnel. This study uses a quantitative research method. The sample used in this study was 80 respondents using the random sampling/probability sampling method with the ara sampling technique. The data analysis techniques are in the form of technical data analysis, descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, partial tests of the coefficient of determination (R Square) as well as path analysis and sobel tests through the SPSS program 25.0 for windows. The results of this study: (1) The Authoritarian Leadership Style Variable (X1) partially affects but is not significant on Work Discipline (Z) with a statistical value of sig. t 0.179 > 0.05. (2) The Variable of Financial Compensation (X2) partially has a significant effect on Work Discipline (Z) with a statistical value of sig. t 0.037 < 0.05. (3) The Authoritarian Leadership Style variable (X3) partially did not have a significant effect on Employee Performance (Y) with a statistical value of sig. t 0.381 > 0.05. (4) The Financial Compensation Variable (X4) partially affects but is not significant on Employee Performance (Y) with a statistical value of sig. t 0.096 > 0.05. (5) The Work Discipline variable (X5) partially has a significant effect on Employee Performance (Y) with a statistical value of sig. t 0.000 < 0.05. (6) There is an influence but not significant Authoritarian Leadership Style (X6) on Employee Performance (Y) through Work Discipline (Z) with an r value of 0.076 and the calculation value of 1.292 < ttable 1.991. (7) There is an influence but not significant Financial Compensation (X7) on Employee Performance (Y) through Work Discipline (Z) with an r value of 0.118 and a calculation value of 1,963 < a table of 1,991.